INTEGRASI NILAI- NILAI BIRRUL WALIDAIN DALAM TRADISI SUNGKEMAN : STUDI ETIKA KOMUNIKASI ANAK TERHADAP ORANG TUA DALAM PERNIKAHAN ADAT JAWA MASYARAKAT DESA SECANG KEC. NGOMBOL KAB. PURWOREJO - Rosid Alfianto; Mahmud Nasir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the integration of birrul walidain values within the sungkeman tradition in Javanese traditional marriage ceremonies among the people of Secang Village, Ngombol District, Purworejo Regency. The study is motivated by the shift in children’s communication ethics toward parents amid modernization, which has contributed to the decline of politeness and respect within the family environment. The sungkeman tradition is perceived not merely as a cultural ritual, but also as a medium for internalizing Islamic educational values, particularly birrul walidain. This research employed a qualitative method with a phenomenological approach. Data collection techniques included observation, interviews, and documentation. The findings reveal that the sungkeman tradition embodies values of respect toward parents, humility (tawadhu’), polite communication (qaulan kariman), apology, and requests for parental blessings. These values are reflected in children’s behavior and communication ethics toward parents within the Javanese traditional wedding procession. Furthermore, the sungkeman tradition demonstrates the harmonization between local Javanese culture and Islamic teachings, which continues to be preserved by the people of Secang Village as a form of cultural preservation and moral education within the family.